1999
DOI: 10.1177/019263659908360303
|View full text |Cite
|
Sign up to set email alerts
|

Professional School Counselors: Inservice Providers Who tan Change the School Environment

Abstract: Professional school counselors can have a significant effect on a school's environment. The skills and knowledge they possess can be shared with teachers and students. Through inservice training opportunities for teachers and classroom activities with students, counselors can develop a more positive environment for student learning and growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In addition to school counselors' important positioning at the center of data flow involving students, others have asserted that school counselor training prepares them with knowledge and skills that can affect broader educational issues that impact schools and the students within them (Clark & Stone, 2007;Kern, 1999). Borders and Shoffner (2003) have suggested that school counselor preparation sets school counselors apart from many other school personnel because of their more extensive preparation and training in a number of areas.…”
Section: Position and Skill Sets Of School Counselorsmentioning
confidence: 99%
“…In addition to school counselors' important positioning at the center of data flow involving students, others have asserted that school counselor training prepares them with knowledge and skills that can affect broader educational issues that impact schools and the students within them (Clark & Stone, 2007;Kern, 1999). Borders and Shoffner (2003) have suggested that school counselor preparation sets school counselors apart from many other school personnel because of their more extensive preparation and training in a number of areas.…”
Section: Position and Skill Sets Of School Counselorsmentioning
confidence: 99%
“…Counselors can also help interpret student data for use in student and whole-school planning. In addition, they can be instrumental in training faculty and staff on such diverse issues as equity and cultural diversity, leamindteaching styles, inclusion strategies, study skills training, and student behavior problems (Kern 1999).…”
Section: May/june 2001mentioning
confidence: 99%